2003 International Symposium on VLSI Technology, Systems and Applications. Proceedings of Technical Papers. (IEEE Cat. No.03TH8
DOI: 10.1109/ccnc.2004.1286866
|View full text |Cite
|
Sign up to set email alerts
|

Video and audio trace files of pre-encoded video content for network performance measurements

Abstract: Video services are expected to account for a large portion of the traffic in future wireless networks. Therefore realistic traffic sources are needed to investigate the network performance of future communication protocols. In our previous work we focused on video services for 3G networks. We provided a publicly available library of frame size traces of long MPEG-4 and H.263 encoded videos in the QCIF format resulting in low bandwidth video streams. These traces can be used for the simulation of 3G networks. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…An alternative approach is to characterize the traffic of encoded video in the public domain, such as encoded videos available from YouTube, in video traces [22], [23]. The main drawbacks of video traces based on encoded public domain videos are that the exact encoding parameters are unknown and that video quality characterization with the widely used PSNR is impossible as the PSNR evaluation requires the uncompressed video source.…”
Section: Related Workmentioning
confidence: 99%
“…An alternative approach is to characterize the traffic of encoded video in the public domain, such as encoded videos available from YouTube, in video traces [22], [23]. The main drawbacks of video traces based on encoded public domain videos are that the exact encoding parameters are unknown and that video quality characterization with the widely used PSNR is impossible as the PSNR evaluation requires the uncompressed video source.…”
Section: Related Workmentioning
confidence: 99%
“…While the video and audio streams are managed as separate RTP streams [38], the profile was set up to ensure that the ''application'' streams were launched concurrently rather than serially at the same time offset, for the same overall duration. Both streams were set up to commence streaming 60 s into the simulation.…”
Section: The Simulation Modelmentioning
confidence: 99%
“…One stream was observed to peak at 600 Mb/s for a few micro-seconds when it transferred only 3.1 Mb/s in 3 seconds. Fitzek et al [6] observed peak-to-mean values between 15 and 45 for bit-rates of audio/video streams. These studies indicated a high burstiness in traffic patterns for new streaming applications.…”
Section: Motivation and Related Workmentioning
confidence: 99%